2000
DOI: 10.1177/0018726700536002
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity, Complexity and Dynamics in the Membership of Collaboration

Abstract: This paper is concerned with the role that membership structures of inter-organizational collaborations have on the achievement of collaborative advantage in the context of tackling social issues. Based on action research involving participants in a wide variety of collaborative situations, the paper aims to explore the nature of the membership of collaborations in practice. A picture of membership is built up from two perspectives. The first considers the structure of collaboration, and argues that ambiguity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
257
1
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(263 citation statements)
references
References 33 publications
2
257
1
3
Order By: Relevance
“…The leadership challenge, in any case, is concerned with influencing or transforming individuals only (or at least largely) to the extent that such transformation may, in turn, affect the behavior of organizations. Furthermore, research has shown that there is frequently ambiguity and complexity surrounding the membership of collaborations, so there is no clear, consensual sense of who should be influenced or which organizations should be influenced (Huxham & Vangen, 2000a). Secondly, there is a problem with the presumption of specified goals.…”
Section: Leadership Research and Collaborationmentioning
confidence: 99%
See 3 more Smart Citations
“…The leadership challenge, in any case, is concerned with influencing or transforming individuals only (or at least largely) to the extent that such transformation may, in turn, affect the behavior of organizations. Furthermore, research has shown that there is frequently ambiguity and complexity surrounding the membership of collaborations, so there is no clear, consensual sense of who should be influenced or which organizations should be influenced (Huxham & Vangen, 2000a). Secondly, there is a problem with the presumption of specified goals.…”
Section: Leadership Research and Collaborationmentioning
confidence: 99%
“…A deeper analysis of the data in these theme areas has revealed that the issues underlying the themes are much less straightforward in practice than initial practitioner views would suggest. A very central part of the research agenda has therefore been to develop a much deeper theoretical understanding of the issues underlying each theme (Eden, Huxham, & Vangen, 1996;Huxham & Vangen, 2000a;. The theory is practice-oriented in that it both derives directly from data collected during practice and is intended to inform practice .…”
Section: Academy Of Management Journalmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, there are accountability systems which clarify who a cross-sector partnership is accountable to and for what (Geddes and Shand, 2013;Page et al, in press). Finally, there is the degree of openness of membership and clarity of roles (Huxham and Vangen, 2000), which may vary from fixed representation and explicit agreed roles, through to multiple people representing a partner with no pre-set assignment of roles.…”
Section: Governancementioning
confidence: 99%